2004
DOI: 10.1158/1078-0432.ccr-1176-3
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of 2-Deoxy-d-Ribose-Induced Angiogenesis with Rapamycin Counteracts a Thymidine Phosphorylase-Based Escape Mechanism Available for Colon Cancer under 5-Fluorouracil Therapy

Abstract: Purpose: Colorectal neoplasms remain a leading cause of cancer-related deaths. A recognized weakness of conventional 5-fluorouracil (5-FU) therapy relates to expression of the intracellular enzyme, thymidine phosphorylase (TP). Although TP promotes 5-FU cytotoxicity, TP-derived 2-deoxy-D-ribose (dRib) counterproductively stimulates tumor angiogenesis. Here, the newly discovered antiangiogenic drug rapamycin was combined with 5-FU to counteract the potential escape mechanism of dRib-induced angiogenesis.Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…The finding that rapamycin inhibits TP-stimulated migration implicates the activation of p70 S6K in this cellular response, which is consistent with other works showing that rapamycin inhibits the migration of vascular smooth muscle cells or endothelial cells (30)(31)(32). In those studies, the effects of rapamycin were primarily mediated by p27 kip , a cell cycle regulator that may be a downstream target of mTOR.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that rapamycin inhibits TP-stimulated migration implicates the activation of p70 S6K in this cellular response, which is consistent with other works showing that rapamycin inhibits the migration of vascular smooth muscle cells or endothelial cells (30)(31)(32). In those studies, the effects of rapamycin were primarily mediated by p27 kip , a cell cycle regulator that may be a downstream target of mTOR.…”
Section: Discussionsupporting
confidence: 91%
“…81 In addition to its functions as a secreted growth factor, PD-ECGF is involved intracellularly in the metabolism of pyrimidine nucleosides and 5-fluorouracil. 82 Expression of PD-ECGF has been shown in tumour cells, stromal cells, and infiltrating mononuclear cells. 83 It has been hypothesised that human colorectal tumours showing low VEGF expression are more dependent on PD-ECGF as the major proangiogenic factor.…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…Further investigations also revealed that rapamycin has a unique anti-tumor mechanism through the binding with FKBP12 and the inhibition of mammalian target of rapamycin (mTOR), which is a central regulator of proliferation, apoptosis [5,11,37,41], and cell growth by inducing cellcycle arrest in the G 1 phase [7]. These latter pharmaco-logical properties have allowed rapamycin to be recognized recently as a possible chemotherapeutic agent against many solid tumor types including breast [21], colon [15], prostate [50], and renal cell carcinomas [38] with a typical IC 50 < 50 nM.…”
Section: Introductionmentioning
confidence: 99%